Development of a module of sociopsychophysiological support for modern IT as a means of increasing the efficiency of individual and collective activities while preserving their biosocial health - Kuzmina, K.I.; Somik, T.M.; Andon, A.P. (Інститут програмних систем НАН України, 2025)
The main idea of the work is the scientific organization of work and leisure of a modern person, family, school, teams, and the world community with a transitional (from average to individual-typological) moment on the way to the effectiveness of the organization of the tandem «Professional competence - human biosocial health». The purpose of the work is to develop a SPF support module for modern IT as a means of increasing the effectiveness of the activities of an individual and a team while preserving their biosocial health. SPF module is a fundamentally new technology that is approaching automation of management. The possibility of adapting the developed technology «Family medicine at home» in the structure of the SPF module as a reliable modern highly competent SPF support method (interdisciplinary) for preserving the biosocial health of the labor collective is being considered. In a broader scale, the technology «Family Medicine at Home» is considered as the beginning of a fundamentally new understanding of the project culture of today, regarding medicine and human health. In the aspect of digital transformation of the information flow, objective SPF indicators of the individual-typological and rhythmological portrait of the collective are presented: correlation and frequency constellations, resonant frequency and system speed, etc. SPF module - technology should end with a real computer interdisciplinary SPF complex to confirm the priorities in modern human sciences such as human individuality, biorhythmology and computerization, cybernetics, which will contribute to a significant increase in the economic and cultural potential of states.Prombles in programming 2024; 4: 51-76